DEVELOPMENT AND CHARACTERIZATION OF SSR MARKERS FROM FUSARIUM INFECTED BARLEY (HORDEUM VULGARE) CDNA DATA SETS - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2016)
In this study, a collection of 6666 expressed sequence tags (ESTs) deriving from two cDNA libraries (9841 and 24112) constructed under Fusarium infected conditions in Hordeum vulgare were screened to detect and characterize simple sequence repeat (SSR) motifs. Ninety-seven SSRs were identified in ESTs. Trinucleotides were the most frequent repeat (51%), followed by dinucleotides (38%) and tetranucleotides (8%), whereas motif size of pentanucleotides and hexanucleotides was only 1% and 4%, respectively, which is rarely found. Forty-nine SSR-containing EST unigenes were matched with Hordeum vulgare known protein with putative conserved domain via BLASTX. Out of 49 EST-SSRs, 33 of them were successfully used to design primer pairs and further confirmed in seven cultivated barley with significant differences in responses to Fusarium related root rot and head blight diseases. Nineteen of them gave amplification products. A total of 26 alleles were generated from 19 loci. The polymorphic information content (PIC) ranged from 0.28 to 0.60 and the expected heterozygosity (He) varied from 0.22 to 0.61. The seven cultivars were divided into three groups based on 19 SSR markers. These novel EST-SSR markers can be applied for genetic analysis, including marker-assisted selection for fusarium related diseases in barley breeding and genetic diversity analysis.
Keywords: Barley; microsatellites; EST; Fusarium; SIMPLE SEQUENCE REPEATS; HEAD BLIGHT; LINKAGE MAP; MICROSATELLITES; RESISTANCE; DNA; ORGANIZATION; ASSOCIATION; SELECTION; RICE